Status report on the development and application of in vitro techniques for the conservation and use of plant genetic resources - Ashmore, S.E.; International Plant Genetic Resources Institute (1997)
This status report describes the existing techniques for in vitro conservation of plant cells, tissues and organs, their current state of the art, present application and existing problems, identifies priority areas for collaborative research, technology development and transfer and proposes a plan of action to address the priority issues identified.